Sabzi : vibrant vegetarian recipes - Khan, Yasmin (Cook) (W.W. Norton & Company, 2025)
"Lifting its name from the Persian word for "herbs," Sabzi is a collection of more than 80 accessible, plant-forward recipes that celebrate the best of Mediterranean, Middle Eastern, and South Asian flavors. From bountiful salads to fragrant soups, colorful mezze, and heart-warming mains, Yasmin invites home cooks to eat better for the health of people and the planet, while staying connected to the traditional food cultures that make us who we are." --